(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
Plant spacing ensures uniform and optimum plant population and facilitates sufficient natural resources for crop growth which, in turns influences the crop yield positively. An investigation was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, during July to December 2017 to study the influence of plant spacing on the yield of double grained rice cultivar. The study comprised five spacing viz. 25 cm × 15 cm, 25 cm × 10 cm, 20 cm × 15 cm, 20 cm × 10 cm and 15 cm × 15 cm and two rice cultivars viz. a double grained rice cultivar and BRRI dhan49 and a double grained rice cultivar. It was laid out in a randomized complete block design with three replications. The double grained rice cultivar produced taller plant (155.65 cm), longer panicle (23.93 cm), higher 1000-grain weight (25.96) and higher straw yield (6.90 t ha-1), though the higher grain yield (3.68 t ha-1) was found in the test cultivar (BRRI dhan49). Planting at 20 cm × 15 cm produced the highest grain yield (3.70 t ha-1) which was at par with 25 cm × 15 cm, 25 cm × 10 cm and 20 cm × 10 cm while planting at 15 cm × 15 cm produced the lowest grain yield (3.13 t ha-1). The interaction of the double grained rice cultivar with all spacing combinations produced taller plants than the spacing combinations with BRRI dhan49. The higher grain yield (3.52 t ha-1) was found in the double grained rice cultivar with 20 cm × 10 cm spacing which was at par with the spacing of 20 cm × 15 cm and 25 cm × 15 cm, respectively; although BRRI dhan49 always produced the higher yield. The lowest grain yield (3.08 t ha-1) was recorded at the double grained rice cultivar with 25 cm × 10 cm spacing, however, the same treatment produced the highest biological yield (11.23 t ha-1) due to the highest straw yield (8.15 t ha-1). Hence, the spacing 20 cm × 15 cm might be recommended for the higher grain yield in the double grained rice cultivar Res. Agric., Livest. Fish.8(3): 273-279, December 2021